WANPRESTASI PENJUAL DALAM PERJANJIAN JUAL BELI KRATOM DI KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - NIM. A1012191024, PRAJA ASHSHIDDIQY (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT This research is based on the problems encountered by the author in the field regarding the breach of contract by sellers in Kratom or